Exhausted Lag-3+ CD4+ T cells are increased in pediatric Inflammatory Bowel Disease. - Schnell, Alexander; Aicher, Carmen; Schnegelsberg, Philipp; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Rueckel, Aline; Regensburger, Adrian; Wölfle, Joachim; Hörning, André (Clinical and Experimental Immunology, 2025)
T cells are one of the main drivers of inflammatory bowel diseases (IBD). Infliximab (IFX) is used in the treatment of IBD as an anti-inflammatory drug to induce remission by neutralizing TNFα. We determined the individual chemokine/homing receptor and cytokine profile in pediatric IBD patients before and during IFX therapy to identify predictive biomarkers for therapy success. Peripheral blood CD4+ cells from pediatric patients with IBD were immunomagnetically isolated and either directly analyzed by FACS for cell distribution and chemokine/homing receptor expression or evaluated for cytokine production after in-vitro-stimulation. Twenty-one responders (RS) and 21 non-responders (NRS) were recruited. Before IFX therapy, flow cytometry revealed decreased percentages of naïve conventional T cells in pediatric IBD patients. The proportions of CD62-L+ T cells were decreased in both CD and UC therapy responders. The cytokine profile of T cells was highly altered in IBD patients compared to healthy controls (HC). During IFX therapy, the frequencies of conventional memory and regulatory memory T cells expanded in both cohorts. IFX response was marked by a decrease of α4β7+ and IFNγ+ memory T cells in both CD and UC. In contrast, frequencies of Lag-3+ T cells proved to be significantly increased in NRS. These observations were irrespective of the underlying disease. T cells of pediatric IBD patients display an activated and rather Th1/Th17-shifted phenotype. The increased expression of the checkpoint molecule Lag-3 on T cells of NRS resembles a more exhausted phenotype than in RS and HC which appeared to be a relevant predictive marker for therapy failure.
EVALuna2:582625